Ways to improve the competitiveness of the economy (Journal of Economic Research & Business Administration, 2015)
"The cluster development is a method of creation of competitive production on the basis of a complex of branches both firms and coordination of their activity. Southern Kazakhstan, where the cotton cluster is reshaped, has unique capabilities for creation of a textile industry. In the article the reasons of development of a cotton-textilecluster and priorities of regional policy in the solution of this problem are reviewed. "
Keywords: The development of the economy; The development of a cluster system